2014
DOI: 10.1074/jbc.m113.513184
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Co-regulates Oxidative Metabolism and ATP Synthase-dependent Respiration in Pancreatic Beta Cells

Abstract: Background: Nutrients stimulate calcium dependent activation of energy metabolism, in pancreatic beta cells.Results: Glucose-induced ATP synthase-dependent respiration is strictly calcium-dependent, with little or no effect of calcium on the NAD(P)H response.Conclusion: Calcium coordinates oxidative metabolism and respiration in pancreatic beta cells.Significance: Calcium has novel mitochondrial targets downstream of mitochondrial dehydrogenases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 46 publications
10
77
0
Order By: Relevance
“…The molecular mechanisms underlying insulin secretion and glucose metabolism have not been fully elucidated (1)(2)(3)(4)(5)(6). Numerous studies have demonstrated that calcium (Ca 2+ ) plays a pivotal role in insulin secretion from the islets of Langerhans and that altered cellular Ca 2+ homeostasis may be involved in defective insulin release (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms underlying insulin secretion and glucose metabolism have not been fully elucidated (1)(2)(3)(4)(5)(6). Numerous studies have demonstrated that calcium (Ca 2+ ) plays a pivotal role in insulin secretion from the islets of Langerhans and that altered cellular Ca 2+ homeostasis may be involved in defective insulin release (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing glucose enhances whole cell NAD(P)H autofluorescence (FIGURE 4B) (112,147). Much of the signal is localized to the mitochondria in INS-1 832/13 cells (190), due in part to fluorescence enhancement caused by binding to proteins, including complex I.…”
Section: A Nadph/nadp ؉ Poolsmentioning
confidence: 99%
“…ATP is transported into the vesicles by a nucleotide transporter (170), is co-released with insulin (170), and may provide an autocrine signal acting via P2 receptors to modulate insulin release (65). Most references cite an early study by Detimary et al (123) (112). C: cytosolic ATP in a single dissociated mouse islet cell monitored with GO-ATeam1 during a transition from 2.8 to 25 mM glucose and following oligomycin (506).…”
Section: Whole Cell Atp Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this low affinity, mitochondria can accumulate large amounts of Ca 2ϩ during cell stimulation when exposed to microdomains of high Ca 2ϩ concentration (21), forming in the vicinity of intracellular Ca 2ϩ release or plasma membrane Ca 2ϩ entry channels (22,23). Mitochondrial Ca 2ϩ uptake activates several Ca 2ϩ -dependent matrix enzymes that stimulate energy metabolism (24,25) and ATP synthase-dependent respiration (26). Prolonged (pathological) accumulation of Ca 2ϩ in the matrix space can lead to mitochondrial Ca 2ϩ overload, followed by mitochondrial permeability transition pore opening (27)(28)(29), resulting in the activation of cell death signals (30,31).…”
Section: Camentioning
confidence: 99%